Pengaruh Senam Diabetes Melitus (DM) Terhadap Perubahan Tekanan Darah Pada Pasien DM TIPE 2 Di Persadia Unit RSUD Dr. Moewardi Di Surakarta Tahun 2015 - Amalia Nuril Afifah; Akhmad Rifa’i (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Type 2 Diabetes Mellitus, Blood Pressure, Gymnastics Diabetes. Diabetes Mellitus is a chronic metabolic disease or disorder with multiple etiologies is characterized by high blood sugar levels. World Health Organitation (WHO) said Indonesia ranks the seventh in the world as a country with the number of people with diabetes mellitus. More than 50% of patients with type 2 diabetes have hypertension (Sweetman, 2009). Management of diabetes disease that has been known there are three ways, namely arranging food, exercise, and medication. Exercise can cause the growth of new capillary blood vessels so as to reduce the blockage in the blood vessels which means it can lower blood pressure. The Objective of the research is to explain the influence of diabetes mellitus exercise to changes in blood pressure in patients with Type 2 diabetes mellitus in Persadia Hospital Dr. Moewardi Surakarta 2015. This type of research is quasy exsperiment to design one group pre and post test design, and data analysis used is frequency distribution univariate and bivariate test with paired samples t-test. Results of this study had a effect of diabetes mellitus exercise to changes in blood pressure in patients with Type 2 diabetes mellitus in Persadia Hospital Dr. Moewardi Surakarta. This is evidenced by paired sample t-test which obtained p value systole 0.01 and diastole 0.018 (p <0.05).The conclusion of the research there is the influence of diabetes mellitus exercise to changes in blood pressure in patients with Type 2 diabetes mellitus in Persadia Hospital Dr. Moewardi Surakarta.